Conspiracy Reflected In Charles Dickens' Oliver Twist (1838) : An Individual Psychological Approach - Muhardian, Adin Widhiatma; , Dr. Phil Dewi Candraningrum; , Titis Setyabudi, S.S, M.Hum (2015)
This Study is about conspiracy. The problem of this study is what conspiracy expressed in Oliver Twist novel. The object of the study is Oliver Twist novel by Charles Dickens. It employed an individual pshycological approach. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the novel and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusion. Based on the analysis it is clear that there is a close relation between this novel and the individual reality in England in early nineteenth century. Dickens wants to explore the conspiracy of England in early nineteenth century through Oliver Twist novel.